Social Entrepreneur: A ‘Coin’ Fundraising Model for Social Organizations - Azwar Anas, M Y (KnE Social Sciences, 2018)
This study aims to make a fundraising model conducted by a social organization with the strengths on social capital, religious values, and social entrepreneurship as an effort to develop the local economy operated by the Nahdlatul Ulama’s zakat and infaq institution. The society movement phenomenon of collecting coins or money worth from IDR (Indonesian Rupiah) 500, IDR 1000, and more, can be followed by all levels of society – both the poor and the rich. It becomes unique that the small value of money can be a huge financial power when collected together. This research employs qualitative research approach with grounded theory method. The implementation of coin fund collection model was conducted by an Islamic organization of Nahdlatul Ulama in Tulungagung regency that was chosen as a case portraying a model of coin fund movement as the social organization’s self-reliance. The data were collected through interviewing the management of the Nahdatul Ulama at the provincial and district levels who run the independent coin fund collection program, in addition, interviewing the members of the organization who were directly involved in the program. The strength of this research is the fundraising model from all communities who are were the members of the social organizations. If the small value of money donated by the community is collected in a very large and sustainable amount, it will have a very significant impact. This is different from the Corporate Social Responsibility (CSR) funds operated by a company as a social responsibility that has an intention to build the company’s brand and expand the company’s market share. Keywords: fundraising, self-reliance coins, social company